Stress corrosion cracking behavior of zirconia ALD–coated AZ31 alloy in simulated body fluid. Issue 6 (18th December 2019) - Peron, Mirco; Berto, Filippo; Torgersen, Jan
Abstract: In the last decades, the interest in magnesium (Mg) and its alloys for biomedical implant devices has been continuously increasing due to their excellent biological and mechanical compatibility with human bones. However, their susceptibility to corrosion‐assisted cracking phenomena, such as stress corrosion cracking (SCC) and corrosion fatigue, in presence of the simultaneous action of corrosive human‐body‐fluid and mechanical loadings has hampered their use in these applications. Developments in this field are thus highly claimed, and this work aims to respond to this need. The effect of a 100‐nm‐thick zirconia coating produced by means of atomic layer deposition on the SCC susceptibility of AZ31 alloy has in fact been investigated carrying out slow strain rate tests at a strain rate equal to 2.6 × 10 ‐6 s ‐1 . The samples were immersed in simulated body fluid at 37°C for the whole duration of the tests. The presence of the coating has revealed to provide a reduction in the SCC susceptibility, measured by means of the ISCC indexes. The improved SCC behavior of the coated samples has been explained by means of corrosion experiments, ie, potentiodynamic polarization curves and hydrogen evolution experiments.